The Role of Artificial Intelligence in Programming Education and Its Impact on the Learning Process - Bagas Dwiantoro; Yudianto Sujana; Puspanda Hatta (IJIE (Indonesian Journal of Informatics Education), 2025)
The integration of Artificial Intelligence (AI) into programming education has rapidly expanded, offering both promising opportunities and complex challenges. This study conducts a systematic literature review (SLR) using the PRISMA framework to examine the influence of AI tools on creativity, collaboration, and technology acceptance in programming education. A total of 33 peer-reviewed studies published between 2022 and 2024 were analysed to explore the pedagogical impact of AI. The findings indicate that AI tools support creative problem-solving, enhance collaborative learning, and increase student engagement through personalized feedback and adaptive learning environments. Despite these benefits, concerns remain about the potential for over-reliance on AI, reduced critical thinking, and ethical issues such as bias and authorship. While AI encourages iterative and imaginative approaches to programming, its successful implementation depends on instructional strategies that promote reflection, responsible tool use, and alignment with real-world programming practices. This study emphasizes the importance of balancing the advantages of AI with thoughtful pedagogy to support meaningful learning. Future research is recommended to investigate the long-term effects of AI on student development and to refine frameworks for integrating AI tools into programming education.